POLICY IMPLEMENTATION IN ACHIEVING BASIC COMPLETE IMMUNIZATION AND UNIVERSAL CHILD IMMUNIZATION INDICATORS IN KAPUAS DISTRICT IN 2018 - Vela, Lia Rosi; Sjaaf, Amal Chalik (Journal of Indonesian Health Policy and Administration, 2020)
Completing the basic immunization and implementing Universal Child Immunization (UCI) are the objectives for the Immunization Program according to the Ministry of Health of Republic Indonesia Strategic Planning. In 2017, Kapuas district achieved 66,6% of the Completed Basic Immunization target and 32,2% of the Universal Child Immunization (UCI) target. There is still a 26,4% gap and a 62,8% gap, respectively, from the 95% target of Strategic Plan Ministry of Health 2015-2019. This study aims to discuss the performance of policy implementation of Completed Basic Immunization (CBI) and Universal Child Immunization (UCI) in 2018 at Kapuas Regency, using qualitative research with case study design at 6 Puskesmas in Kapuas Regency. The total informants in this research are 34 informants. The study showed that the performance of policy implementation regarding indicator achievement of CBI and UCI of Kapuas Regency in 2018 have not been optimal. So, policy improvement is needed to increase CBI and UCI achievement of Kapuas Regency next year